STRATEGI HEDGING TURKI DAN IMPLIKASINYA TERHADAP RESPONS NATO ATAS PERANG RUSIA-UKRAINA (2022-2025) - Rachel Kumendong; Beatrice Sungkono; Bias Permata; Kayla Yosin (Mandala: Jurnal Ilmu Hubungan Internasional, 2025)
This article aims to analyze Turkey’s hedging strategy in the context of the Russia–Ukraine war (2022–2025) and its implications for NATO’s response. Since Russia’s invasion of Ukraine on February 24, 2022, Turkey—as a NATO member—has demonstrated a distinct response compared to other alliance countries. Instead of imposing economic sanctions on Russia, Turkey chose to maintain relations in various sectors, raising doubts about the consistency of its commitment to preserving alliance cohesion. This study employs a qualitative method with a focus on literature review to explore the dynamics of Turkey’s foreign policy. The main research question posed is: to what extent has Turkey’s hedging strategy in the Russia–Ukraine war affected NATO’s cohesion and response toward Russia? The findings suggest that Turkey’s hedging strategy does not merely weaken the alliance’s cohesion but also opens opportunities for NATO to enhance its deterrence capability against Russia while supporting Ukraine’s struggle.